Spatiotemporal patterns of prevalence and mortality from respiratory infections and tuberculosis across Japan and its prefectures - Xiaohui Li; Gang Wu; Zhimin Ding (PLoS ONE, 2026)
Background Respiratory infections and tuberculosis (RIT) remain major contributors to global morbidity and mortality. In rapidly ageing societies, demographic shifts may decouple disease occurrence from fatal outcomes. Japan offers a representative setting to examine long-term spatiotemporal patterns of RIT burden in an advanced ageing context. Methods A population-based spatiotemporal analysis of Japan from 2010 to 2023 was conducted using standardized national and prefectural estimates. Annual RIT prevalence and deaths were examined by sex and age group. Long-term trends were quantified using estimated annual percentage change (EAPC) from log-linear models of rates, and changes in the etiological composition of RIT mortality were assessed by age and sex. Results National RIT prevalence fell from 31.40 million cases in 2010 to 27.52 million in 2023, and the prevalence rate decreased from 24,536.02 to 22,070.66 per 100,000 (EAPC −1.11). In 2023, prevalent cases were similar between females (13.95 million) and males (13.57 million). Adults aged 75 years and older increased from 2.47 million prevalent cases in 2010 to 3.28 million in 2023 despite declining rates. Total RIT deaths decreased from 104,048 in 2010–98,091 in 2023, while the death rate changed from 81.31 to 78.68 per 100,000 (EAPC 0.83). Mortality remained higher in males than females, with 61,683 versus 36,407 deaths in 2023, and was concentrated in adults aged 75 years and older (87,545 deaths), although their death rate declined from 629.40 to 429.91 per 100,000. Across prefectures, prevalence rates declined universally (−8.47% to −56.30%), whereas deaths increased in most prefectures (−10.74% to 153.64%), with the largest rises observed in Saitama (153.64%), Chiba (130.41%), and Osaka (63.79%). Etiology-specific patterns shifted, with Streptococcus pneumoniae declining from 28.9% to 20.4% of deaths, while Staphylococcus aureus rose from 12.2% to 19.0% and Legionella spp. from 8.6% to 11.5%, most notably among adults aged 75 years and older. Conclusions In ageing settings exemplified by Japan, declining RIT prevalence can coexist with persistent, older-adult–concentrated mortality, subnational inequality, and an evolving etiological profile. Age-focused care, prefecture-tailored prevention, and etiology-aware management may reduce avoidable deaths and geographic disparities.